Complications and Long-Term Outcome in 16 Canine Cementless Hybrid Hip Arthroplasties - Bayer, Karol; Matiasovic, Matej; Steger, Helmut; Böttcher, Peter (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The purpose of this study was to retrospectively evaluate the complications and long-term outcomes of total hip arthroplasty (THA) using a hybrid cementless system.Materials and Methods Medical records of dogs that underwent THA using a combined implant system consisting of Innoplant Screw Cup, Kyon taper head and Zurich cementless (Z-THA) stem between March 2010 and March 2015 were reviewed. Dogs with a minimum follow-up of 2 years were included. Signalment, complications and outcome at the latest follow-up examination were recorded.Results Sixteen hybrid THA were performed in 12 dogs. Mean follow-up was 42.5 months. Overall complications occurred in three arthroplasties (19%) including luxation (n = 1), aseptic cup loosening (n = 1) and implant failure with screw breakage followed by stem subsidence (n = 1). Two arthroplasties including prosthesis luxation and aseptic cup loosening were successfully revised using the here described hybrid system and achieved full functional outcome at the last follow-up examination. One arthroplasty with screw breakage and secondary stem subsidence was treated conservatively and achieved an acceptable outcome.Conclusion Hybridization of the Innoplant Screw Cup, Kyon taper head and Zurich cementless for initial THA surgery is feasible. In comparison with the reported complications and outcomes for single implant THA systems, the hybrid THA did not prove to have greater clinical benefits for use in primary THA surgery.
Keywords: total hip arthroplasty; total hip replacement; Helica; Kyon